Case Report and review of the literature: A rare cut – surgical resection of primary CNS EBV- positive T-cell lymphoma - Anastasopoulos, Lykourgos; Charalampopoulou, Eirini; Argyrakos, Theodoros; Bourlogiannis, Fotis; Korfias, Stefanos (Frontiers in Oncology, 2025)
Primary central nervous system T-cell lymphoma (PCNS-TCL) is an exceptionally rare entity, representing less than 5% of all PCNSLs. Its diagnosis is frequently delayed due to nonspecific radiologic features and an often absent or poor response to corticosteroid therapy. Here, we present a unique case of an immunocompetent 58-year-old male with a solitary, EBV-positive, T-cell lymphoma localized in the right temporal lobe. The lesion was refractory to corticosteroid therapy and ultimately required gross total resection (GTR) due to progressive neurological deterioration. Postoperative histopathological examination confirmed a cytotoxic T-cell phenotype with EBV positivity. The patient demonstrated immediate neurological improvement post-surgery. This case underscores the importance of considering T-cell lymphoma in the differential diagnosis of solitary intracranial masses and suggests that surgical intervention may be warranted in select cases.